The Effect of Adding Lumut Banana Fruit Juice in Egg Yolk Citrate Diluent on The Quality of Duroc Boar Spermatozoa - Baba, Derma Melian Putriani; Setyani, Ni Made Paramita; Telupere, Frangky M.S; Marawali, Aloysius (Journal of Tropical Animal Science and Technology, 2025)
The aim of this study was to evaluate the use of Ambon green banana extract (SBPAL) in citrate-egg yolk extender (SKT) to preserve Duroc boar semen at a storage temperature of 18-20°C. The study material consisted of healthy Duroc boar semen aged 2 years, accustomed to semen collection. The experiment used a completely randomized design (CRD) with six treatments and five replications: P0 = 100% SKT, P1 = 100% SKT + 10% SBPAL, P2 = 100% SKT + 15% SBPAL, P3 = 100% SKT + 20% SBPAL, P4 = 100% SKT + 25% SBPAL, P5 = 100% SKT + 30% SBPAL. The variables measured included motility, viability, abnormalities, and spermatozoa longevity (LTH). The results showed that the P4 treatment produced the highest spermatozoa quality statistically (P<0.05) compared to the other treatments, with motility: 46.00±2.12%, viability: 53.74±2.42%, abnormality: 4.47±0.84%, and spermatozoa LTH: 55.28±2.40 hours. In conclusion, the addition of 25% SBPAL in the SKT extender effectively maintained the quality of Duroc boar spermatozoa for up to 48 hours of storage.